Factors associated with post NICU discharge exclusive breastfeeding rate and duration amongst first time mothers of preterm infants in Shanghai: a longitudinal cohort study - Xin Jiang; Hui Jiang (BMC, 2022)
Abstract Background Breastfeeding is crucial for the preterm infants. Breast milk is not only food but also medicine. Few studies have focused on the longitudinal effects of exclusive breastfeeding outcome of preterm infants separated from their mothers after discharge, especially in Shanghai. We aimed to examine the exclusive breastfeeding rate and duration amongst first time mothers of preterm infants after discharge and its determinants. Methods Analyses were based on 500 preterm infants separated from their mothers in a tertiary maternity and infant-specialized hospital in Shanghai from September 2018 to September 2019.The Socio-demographic characteristics, breastfeeding knowledge questionnaire, breastfeeding self-efficacy short form scale, Edinburgh postpartum depression scale and breastfeeding family support scale were used for the investigation and the exclusive breastfeeding rate of premature infants was followed up on 1 month, 3 months and 6 months after discharge. The changing trend of breastfeeding knowledge, breastfeeding self-efficacy, postpartum depression and family support were measured by ANOVA at different stages. Using the chi-square test and multiple logistic regression, factors impacting the breastfeeding rate of preterm infants at three time intervals after discharge were investigated. The Kaplan Meier survival curve and cox regression model were used to analyze the determinants of exclusive breastfeeding duration of premature infants after discharge. Results Exclusive breastfeeding rates were 19.0, 17.2 and 10.4% at 1 month, 3 months and 6 months after discharge of preterm infants, respectively. The average length of exclusive breastfeeding duration was(3.69 ± 1.80)months. Finally, type of delivery (adjusted odds ratio [AOR] 1.564; 95% confidence interval [CI] 0.513,3.116), gestational age(AOR 0.612, 95% CI 0.236, 3.418), maternal family support (AOR 6.125,95% CI 6.359, 98.452) were discovered to be independent predictors on the exclusive breastfeeding rate at 6 months after preterm infants were discharged. Through the cox regression model, we found that a maternal planned pregnancy (HR 0.681, 95%CI 0.531,0.873), delivering breast milk during hospitalization (HR 0.797, 95%CI 0.412,2.288), NICU feeding mode during hospitalization (HR 1.221, 95%CI 0.128,1.381) and family support (HR 0.561, 95%CI 0.004,2.428) were significantly associated with the exclusive breastfeeding duration after discharge. Conclusions The exclusive breastfeeding outcome of premature infants was affected by many factors, so we should focus on the three levels of individual, family, society and design targeted intervention measures to increase the exclusive breastfeeding rate and prolong exclusive breastfeeding duration.